Manager Factor Associated to the Compliance of Local Smoke-Free Regulation among Star Hotels in Badung District - Ni Luh Putu Devhy; Putu Ayu Swandewi Astuti; Dyah Pradnyaparamita Duarsa (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: Smoke-free area regulation has been issued recently in Bali Province and Badung District. This study aimed to identify factors associated to the compliance of local smoke-free regulation in star hotel. Methods: This study was a cross-sectional analytic study conducted in Badung District from March to May 2014. Samples were 104 hotels and the managers that selected using systematic random sampling. Compliance data collected through observation using the observation form and the data of managers through interviews using a structured questionnaire. Data were analyzed using chi-square test and poisson regression. Result: The results shows that the compliance of star hotels to local smoke-free regulation was low (15.4%). The concrete support of hotel managers was significantly associated with the compliance to smoke free regulation (PR=4.25; 95%CI: 1.03-17.58). The factors that not significantly associated to the compliance were the knowledge (PR=2.0; 95%CI: 0.8-4.9), attitude (PR=2.5; 95%CI: 0.8-8.2), and organization support (PR=1.8; 95%CI: 0.7-4.5). Furthermore the hotel compliance of managers who have smoking behavior was 0% while the managers without smoking behavior, the compliance was 19.5%. Conclusion: The compliance of star hotels in Badung District on the implementation of local smoke-free regulation was relatively low and the compliance was associated with the presence of concrete support of the hotel managers.